Social justice, empowerment and sustainability. How guidance could enhance a critical consciousness for life-long learning - Coccimiglio, Cristina; Garista, Patrizia (Form@re - Open Journal per la formazione in rete, 2019)
Which kind of connection can we have in Italy between sustainability and adult education within the educational and regulatory system? Which kind of international and European perspectives allow us to frame this connection and reshape it in methodological choices for didactics in adult education? This paper proposes a reflection on topics such as social justice, empowerment and adult education, considering authors’ participation in mutual learning initiatives, in Europe and Italy, finalized to the implementation of strategies to improve key and transversal skills. Specifically, this reflection focuses on guidance, and aims to analyse it with the lens of critical education research as it investigates the connection among social justice, empowerment, education and well-being. Giustizia sociale, empowerment e sostenibilità. Come l’orientamento può sostenere una coscienza critica nel life-long learning Quale connessione ci può essere in Italia, nel sistema formativo e normativo, tra sostenibilità e istruzione degli adulti? Quali prospettive internazionali ed europee permettono di inquadrare questa connessione e di rimodularla in scelte metodologiche per la didattica nell’istruzione degli adulti? Il presente contributo propone una riflessione sui temi quali la giustizia sociale, l’empowerment e la formazione degli adulti, considerando la partecipazione degli autori a iniziative di mutual learning, in Europa e in Italia, finalizzate all’implementazione di strategie per migliorare le competenze chiave e trasversali. Tale riflessione si concentra sull’orientamento, e lo analizza in rapporto alla ricerca didattica dei critical educators, interessati al rapporto tra giustizia sociale, empowerment, educazione e benessere.